The Environmental Education on the Ethical Development Problem - González-Escobar, Carlos Humberto (2017)
The objective of this literature review is to understand the complexity of the environmental issue in a context of civilizational crisis generated by the scientific paradigm and the prevailing forms of knowledge. From this research, the objective is to evaluate the pedagogical exercise and the role of the environmental education in the supreme task of forming a cognitive, ethical, political, and historical subject capable of taking the new planetary challenges on. The structural order of this essay focuses on a critical reflection on the environmental crisis; it also questions the restrictions of the environmental education, and, from the complexity, the reasons for trying to incorporate new fields of study with a transdisciplinary approach. This paper analyzes the structural causes of the discourse of development as factors that generate the social, political and environmental conflict in Colombia. These causes are reflected in an institutional crisis, absence of the State, and, therefore, in governability; for which education makes possible a pedagogical exercise in a critical formation that leads to a configuration of democracy and public management. The exercise of power, the decision-making and the role of human subjects must be accomplished in a conscious and ethical way (integrative values). In order to achieve this, an ethics of development is essential to understand and assume responsibility for environmental issues. It is understood, then, that the development supports an ethical dimension promoting sustainable interactions between the society and the nature.